Graphene‐Nanowall‐Decorated Carbon Felt with Excellent Electrochemical Activity Toward VO2+/VO2+ Couple for All Vanadium Redox Flow Battery. Issue 4 (31st December 2015) - Li, Wenyue; Zhang, Zhenyu; Tang, Yongbing; Bian, Haidong; Ng, Tsz‐Wai; Zhang, Wenjun; Lee, Chun‐Sing
Abstract : 3D graphene‐nanowall‐decorated carbon felts (CF) are synthesized via an in situ microwave plasma enhanced chemical vapor deposition method and used as positive electrode for vanadium redox flow battery (VRFB). The carbon fibers in CF are successfully wrapped by vertically grown graphene nanowalls, which not only increase the electrode specific area, but also expose a high density of sharp graphene edges with good catalytic activities to the vanadium ions. As a result, the VRFB with this novel electrode shows three times higher reaction rate toward VO2 + /VO 2+ redox couple and 11% increased energy efficiency over VRFB with an unmodified CF electrode. Moreover, this designed architecture shows excellent stability in the battery operation. After 100 charging–discharging cycles, the electrode not only shows no observable morphology change, it can also be reused in another battery and practical with the same performance. It is believed that this novel structure including the synthesis procedure will provide a new developing direction for the VRFB electrode. Abstract : Graphene‐nanowall‐decorated carbon felts are fabricated via an in situ one step method and used as positive electrode for vanadium redox flow battery (VRFB), which shows enhanced electrochemical acitivity toward VO2 + /VO 2+ redox couple, resulting in excellent VRFB peroformance. It is believed that this novel structure including the synthesis procedure will provide a new developing direction for VRFB electrode.